Search 75,714 tutors
FIND TUTORS
Ask a question
0 0

Simplify using distributive property3(-2+x+4)

Tutors, please sign in to answer this question.

3 Answers

 Better Simplify the parenthesis first. It becomes important when things get more complicate.
 
   3 ( -2 + X + 4 ) = 3 ( X + 2) = 3X + 6
 
   Like:
 
    5 - 3 ( -95 + 75 + X)= 5 - 3 ( -15 + X) = 5 + 45 -3X = 50 -3x
 
     You don't have to multiply 3 by 95& 75. 
3 (-2 + x + 4) = -6 +3x +12 = 3x + 6
Multiply the three through (above) then add the -6 to the +12.
 
3x + 6  is your final answer.
 
 
 
distributive property states:  a(b + c) = ab + ac
 
3(-2 + x + 4)
 
in your case you have three values inside the parentheses, so you can use this: 
 
a(b + c + d) = ab + ac + ad
 
so, (3 * -2 + 3x + 12) ---> -6 + 3x + 12 ---> 3x + 6